Interviews that attend to emplacement: the “walk-through” method - Polkinghorne, Sarah; Given, Lisa M.; Carlson, Lauren (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
Within library and information studies (LIS), there is growing awareness of the role of the body and its surroundings in people’s information and knowledge experiences. Predominant data collection methods, such as the sit-down interview, should be reexamined in light of this awareness. This paper examines interview methods theoretically and empirically. First, this paper introduces the concept of emplacement, the interrelationship of body, mind, and place, as a useful lens for challenging conventional interviewing practices. Second, this paper delineates the “walk-through” interview, which in a study of undergraduates’ information behaviours prompted richer detail from participants than did “sit-down” interviews. **Awarded Best Overall Conference Paper **